Potentially Probiotic Limosilactobacillus fermentum Fruit-Derived Strains Alleviate Cardiometabolic Disorders and Gut Microbiota Impairment in Male Rats Fed a High-Fat Diet - de Araújo Henriques Ferreira, Georgianna; Magnani, Marciane; Cabral, Lucélia [UNESP]; Brandão, Larissa Ramalho; Noronha, Melline Fontes; de Campos Cruz, Josiane; de Souza, Evandro Leite; de Brito Alves, José Luiz (Springer Nature, 2022)
High-fat diet (HFD) consumption is a risk factor for dyslipidemias, insulin resistance, and arterial hypertension linked with gut dysbiosis. Probiotic administration has been suggested as a safe therapeutic strategy for gut microbiota modulation and treatment and/or prevention of cardiometabolic disorders. Here, we assessed the effects of a potentially probiotic formulation containing strains of the Limosilactobacillus (L.) fermentum 139, 263, and 296 on the cardiometabolic disorders and gut microbiota derangements provoked by the HFD consumption. Male Wistar rats were allocated into control diet (CTL, n = 6), HFD (n = 6), and HFD receiving L. fermentum formulation (HFD-LF, n = 6) groups for 4 weeks. L. fermentum formulation (109 colony-forming unit (CFU)/ml of each strain) was daily administered by oral gavage. After 4-week follow-up, biochemical measurements, blood pressure (BP), heart rate (HR), sympathetic tone, and gut microbiota composition were evaluated. HFD consumption for 4 weeks increased lipid profile, insulin resistance, sympathetic tone, and blood pressure and impaired gut microbiota composition in male rats. Administration of L. fermentum formulation improved the gut microbiota composition, lipid profile, insulin resistance, autonomic dysfunction, and BP in rats fed with a HFD. Administration of a potentially fruit-derived probiotic formulation of L. fermentum strains improved gut microbiota composition and alleviated hyperlipidemia, insulin resistance, and sympathetic hyperactivity and increased BP in rats fed a HFD. Our findings may encourage the development of randomized controlled trials to assess the effects of L. fermentum treatment in subjects with cardiometabolic disorders.
Keywords: Blood pressure; Dyslipidemia; High-fat diet; Limosilactobacillus fermentum; Probiotic